SENTENCING АND ENFORCEMENT OF THE PRISON SENTENCE SERVED IN THE PREMISES WHERE THE CONVICTED PERSON RESIDES (THE SO-CALLED HOUSE ARREST) - Milić, Ivan; Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The rule that convicted persons serve their sentences exclusively in prisons has not been valid in the Republic of Serbia for a long time. Prison sentences may also be executed in the premises where the convicted person resides. Such a solution is introduced by the 2009 Law on Amendments and Supplements to the Criminal Code.The Criminal Code does not prescribe the punishment of a prison sentence served in the premises where the convicted person resides as a special punishment. Instead, the offender is sentenced to imprisonment, which is then executed in the premises where he lives. In criminal proceedings, the court is obliged to individualize the criminal sanction in a way that takes into account objective and subjective circumstances - the circumstances relating to the committed crime and its perpetrator. There are such perpetrators who it is necessary to sentence to prison, but who should not be sent to a penal institution. The prison sentence may also be served in premises where they reside (with or without electronic surveillance).Although, in a legally-binding sentence, the accused is sentenced to imprisonment in a penal institution, this does not necessarily mean that he will be placed into a penal institution to serve his sentence. The ammendments and supplements of the Criminal Code leave an „opportunity“ for the convict to serve his sentence in the premises where he resides, if the prescribed conditions are met. This is only a possiblity which may be decided on by the judge in charge of executing criminal sanctions.If it is decided that the convicted person shall serve his sentence in the premises where he resides, the next step is the execution of the sentence. Not all convicted persons who are serving their sentence in this way are in the same legal position, as there is individualization in the process of executing a sentence as well. This difference is apparent, above all, in the amount of time that a convict is allowed to spend outside of the premises in which he resides.The focus of the authors’ attention is precisely the punishment of imprisonment served in the premises where the convict resideds (the so-called house arrest). The authors deal with material aspects and aspects of execution of the sentence. This paper focuses, among other matters, on the conditions for sentencing, models of execution of the sentence and the legal position of the convicted person while serving his sentence.
Keywords: prison sentence, house arrest, sentencing, execution, court, individualization.